The impact of regulation on construction labour productivity - Muhamad Amir Yusof, Sujani (2019)
Labour productivity in the construction industry has significantly declined. Therefore, there is a need to assess construction labour productivity on the present day. Regulation has known as one of the factors that may directly affect productivity. The objective of this study is to find the impact of different regulations on construction labour productivity in Malaysia and identify challenges associated with regulations. Data has been collected by doing individual interview session of 12 respondents from across Malaysia. The analysis has been done by using thematic analysis which is a qualitative method of analysis. The results show that regulations give an impact on the construction labour productivity positively and negatively in term of time, cost, process and human resources. The challenges that have been caused by enforcement of regulation are time constraints, bureaucracy, management, human resources demand, professionalism and etiquette.